2017
DOI: 10.1038/srep45788
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of alirocumab according to background statin type and dose: pooled analysis of 8 ODYSSEY Phase 3 clinical trials

Abstract: Low-density lipoprotein cholesterol (LDL-C) reductions with the PCSK9 monoclonal antibody alirocumab may be affected by background statin dose due to increased PCSK9 levels with higher statin doses. Data from 8 Phase 3 trials conducted with background statin (n = 4629) were pooled by alirocumab dose (75 or 150 mg every 2 weeks) and control (placebo/ezetimibe), and analyzed by background statin type/dose. Overall, 58.4% received high-dose statins (atorvastatin 40–80 mg, rosuvastatin 20–40 mg, simvastatin 80 mg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The option -a AGATCGGAAGAGCACACGTCTGAACTCCAGTCAC and -A AGATCGGAAGAGCGTCGTGTAGGGAAAGAGTGTAGATCTCGGTGGTCGCCGTATCATT were used for the common adapter sequence of the Illumina TruSeq adapters and the option −q 0, −m 20, −O 3 was used for trimming low quality 5′ and 3′ ends of the raw reads. The cleaned high quality reads after trimming the low quality bases and sequencing adapters were mapped to the mouse reference genome mm10 of the UCSC genome ( https://genome.ucsc.edu ) by STAR software 50 . Since the sequencing libraries were prepared strand-specifically by using Illumina’s strand-specific library preparation kit, the strand-specific library option,–library-type fr-firststrand was applied in the mapping process.…”
Section: Methodsmentioning
confidence: 99%
“…The option -a AGATCGGAAGAGCACACGTCTGAACTCCAGTCAC and -A AGATCGGAAGAGCGTCGTGTAGGGAAAGAGTGTAGATCTCGGTGGTCGCCGTATCATT were used for the common adapter sequence of the Illumina TruSeq adapters and the option −q 0, −m 20, −O 3 was used for trimming low quality 5′ and 3′ ends of the raw reads. The cleaned high quality reads after trimming the low quality bases and sequencing adapters were mapped to the mouse reference genome mm10 of the UCSC genome ( https://genome.ucsc.edu ) by STAR software 50 . Since the sequencing libraries were prepared strand-specifically by using Illumina’s strand-specific library preparation kit, the strand-specific library option,–library-type fr-firststrand was applied in the mapping process.…”
Section: Methodsmentioning
confidence: 99%
“…In studies on Japanese patients (with or without heFH), alirocumab treatment reduced LDL-C levels by at least 40% [20,21]. Similar to the results observed in this Korean population, a pooled analysis of eight ODYSSEY phase 3 trials (n = 4,629) indicated that alirocumab provided consistent reductions in LDL-C regardless of the statin dose and type [25]. In the ODYSSEY LONG TERM trial (n = 2,341), TEAEs were observed in 81% of alirocumab-treated patients [19], which is more than that observed in the Korean cohort (45%).…”
Section: Discussionmentioning
confidence: 69%
“…The safety and efficacy observations with alirocumab in this open-label program, which included very high-risk and difficult to treat patients with uncontrolled LDL-C who had exhausted other lipidlowering treatment options, were consistent with those in the ODYSSEY trials 4,5,7,8,16,17 as well as pooled subanalyses of patients with HeFH 6 and by statin type and dose. 18 Although this expanded use program required patients to be on maximally tolerated statin therapy as in the majority of ODYSSEY trials, this program was distinct from most ODYSSEY trials (which permitted only simvastatin, atorvastatin, or rosuvastatin) as patients were permitted to use all available statins. Moreover, patients who were documented as being unable to tolerate any dose of statin were included in the program.…”
Section: Discussionmentioning
confidence: 99%